Programmed Instruction: With Emphasis on Accounting. - Buckley, John W. (The Accounting Review, 1967)
Abstract This article focuses on a study which analyzed the role of programmed instruction in accounting instruction. Higher education is the poorer for not requiring basic teacher-training and/or educational psychology as prerequisites for academic appointments. The assumption that the post-baccalaureate process per se produces "good" teachers may not be a valid one. For many accounting instructors who wish to experiment with these new methods for communicating accounting verbal and manual skills it means starting at the elementary level of learning theory. Knowledge of the over-all learning process is essential not only as an aid to introducing and testing programs, but also as a means for selecting from among competing programs the program that is best suited pedagogically to the specific learning experience. Educational psychology contains a wealth of concepts and theories relating to the learning process, e.g., learning efficiency, task-orientation, identification, concept recognition, concept association and transfer, motivational or readiness factors.